Innate Sex Differences in the Timing of Spring Migration in a Songbird - Maggini, Ivan (Public Library of Science, 2012)
In migrating animals protandry is the phenomenon whereby males of a species arrive at the breeding grounds earlier than females. In the present study we investigated the proximate causes of protandry in a migratory songbird, the northern wheatear Oenanthe oenanthe. Previous experiments with caged birds revealed that males and females show differentiated photoperiod-induced migratory habits. However, it remained open whether protandry would still occur without photoperiodic cues. In this study we kept captive first-year birds under constant photoperiod and environmental conditions in a “common garden” experiment. Male northern wheatears started their spring migratory activity earlier than females, even in the absence of environmental cues. This indicates that protandry in the northern wheatear has an endogenous basis with an innate earlier spring departure of males than females.